Chapter 16 (Un)conscious Perspectival Shape and Attention Guidance in Visual Search A Reply to Morales, Bax, and Firestone (2020) - Henke, Benjamin (Taylor & Francis, 2024)
When viewing a circular coin rotated in depth, it fills an elliptical region of the distal scene. For some, this appears to generate a two-fold experience, in which one sees the coin as simultaneously circular (in light of its 3D shape) and elliptical (in light of its 2D 'perspectival shape' or 'p-shape'). An energetic philosophical debate asks whether the latter p-shapes are genuinely presented in perceptual experience (as 'perspectivalists' argue) or if, instead, this appearance is somehow derived or inferred from experience (as 'anti-perspectivalists' argue). This debate, however, has largely turned on introspection. In a recent study, Morales et al. (2020) aim to provide the first empirical test of this question. They asked subjects to find an elliptical coin seen face-on from a search array that also included a circular coin seen either face-on or at an angle. They found that subjects reacted more slowly when the distracting circle was seen at an angle, such that its p-shape matched that of the target ellipse. From this, they concluded that the similar p-shape between the ellipse and circle constituted a phenomenal similarity between the two, and thus that perspectivalism is true. We show that these results can also be explained by pre-attentive guidance by unconscious representations (in what follows, just "unconscious pre-attentive guidance") and that this explanation is at least as plausible as one from phenomenal similarity. Thus, we conclude that the experiment does not support perspectivalism over anti-perspectivalism.